Management Of Distance Education Degree Program At The Indonesian Dual Mode University - Prasetyo, Hendro; Suherman, Dadang; Warta, Waska; Cepi Barlian, Ujang (CV. Inara, 2022)
Indonesia needs much more traditional higher education institutions offering distance education (DE) degree programs. However, there is little in the literature that can be used as reference on how to plan and implement the DE program in the Indonesian context. This study aims to help fill the gap in the knowledge by investigating the management of two DE degree programs at two traditional campus universities in Indonesia. Data were collected through in-depth interviews and document reviews using the collective case study approach. The collected data were then analyzed individually within case and across cases to identify similarities and differences. Evidence shows that the decision to open a DE degree program was based on a careful assessment of its market potentials and its compatibility with the institution’s vision and mission. In addition to having clear goal and strategy, the program was also planned, implemented and evaluated in a manner suitable with the unique characteristics of distance education. The results of this study could be used as reference by other universities considering or planning to open a DE degree program.